(untitled) (International Journal of Geoscience, Engineering and Technology, 2024)
The risk of contamination of groundwater is determined by hydrogeological factors, such as the porosity of aquifers, static water pressure, and the attenuation capacity of the upper strata, as well as anthropic factors, such as the distribution of human activities on the surface and subsurface, which influence the quantity, frequency, form of release and chemical properties of the contaminants generated. The objective of this study is to identify the susceptibility to contamination of wells granted in relation to activities licensed at Supram Leste Mineiro, based on the analysis of natural vulnerability in the context of the potential for contamination of groundwater and potentially contaminating activities within a radius of 200 m of the wells. The study reveals that although activities in areas with very low vulnerability predominate, the presence of activities with high to medium potential in the vicinity of wells represents a significant risk to the water table. The 126 wells identified as having some type of human activity in their vicinity represent only approximately 10% of the wells that were granted during the period under analysis. However, it is notable that activities with high polluting potential are present in the areas of influence of 52% of these wells (5.56% related to soil and 46.83% to water), which are intended for human consumption or public supply. The results emphasize the need for measures to protect and manage groundwater resources, such as the implementation of clearer and more effective regulations, and increased supervision and monitoring to ensure the quality of water intended for human consumption and other uses.